Prognostic factors in clear cell carcinoma of endometrium: analysis of 55 cases - Loizzi, Vera; Cicinelli, Ettore; Lepera, Achiropita; Legge, Francesco; Memmola, Massimiliano; Chiarello, Giulia; Arezzo, Francesca; Del Vecchio, Vittoria; Resta, Leonardo; Cormio, Gennaro (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work: The purpose of this study was to evaluate the clinical and pathologic prognostic factors associated with survival in patients with clear cell carcinoma (CCC) of the endometrium. Methods: A retrospective review of fifty-five patients with endometrial clear cell carcinoma were collected. Results: The median overall and disease-free survivals were 40 and 20 months, respectively. A univariate analysis was performed with respect to stage of disease, age, lymph nodes status, myometrium invasion, lymph vascular space invasion and adjuvant therapy. Stage was found to be the only important prognostic factor related to survival. In fact, early stage had a median survival of 77 months compared to 34 months in the advanced disease (p<0.04). These differences remained significant after adjusting for single stage (stage III versus IV). Conclusions: Endometrial CCC is a rare histotype. Advanced stage disease is considered a poor prognostic factor. Recurrences are high even in early stage. Randomized clinical trials are needed.